STUDI TENTANG METODE PENYULUHAN YANG DIGUNAKAN PENYULUH DALAM MENYAMPAIKAN MATERI PENYULUH KEPADA PEMBUDIDAYA IKAN DI KECAMATAN TENGGARONG SEBERANG - Achmad Khoiruddin; Helminuddin; Eko Sugiharto (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
The purpose of this research is examine the counseling methods used by Fisheries Instructors in Delivering Information to Fish Farmers in districts Tenggarong Seberang. The sampling method used was the Purposive Sampling method with a total of 10 person. Data analysis method used is Interactive analysis method with the analysis model of data collection, data condensation, display data and conclusion. The results of this study showed that there are two methods used by fisheries instructors in providing information to fish farmers in Tenggarong Seberang, namely the method of individual approach and group approach. Methods that include individual approaches are individual method while methods included in the group approach are demonstration methods and lectures.Keywords: Counseling Methods, Fish Cultivators Group, districts Tenggarong Seberang.